Adaptability-Agility Synergies in Micro-Retail: Dynamic Capabilities and Supply Chain Performance in Emerging Market Nanostores - Ortega-Jimenez, Cesar H; Melgar-Martínez, Narciso A; Sabillon Palomeque, Dany N.; Calix Melendez, Flavio L.; Cruz Amaya, Jennifer Daniela (LACCEI, 2025)
Dynamic capabilities theory faces critical limitations when applied to micro-enterprises, where resource constraints fundamentally alter capability development requirements. This study provides the first comprehensive examination of two novel theoretical constructs, micro-enterprise capability synergy theory and resource-constrained dynamic capabilities theory, by examining how adaptability-agility integration influences supply chain performance in nanostores—the backbone of emerging market retail representing 90% of businesses yet remaining theoretically underexplored. Using canonical correlation analysis on 170 Honduran nanostores, we examine relationships between 31 capability indicators and 40 performance measures. Results reveal unprecedented capability-performance relationships (r = 0.862, p < 0.002) explaining 74.3% of performance variance—effect sizes substantially exceeding those in large organizations. Critically, integrated capabilities generate synergistic rather than additive effects, with capability integration yielding 38% higher profitability and 30% better inventory turnover compared to individual capability approaches. This research validates scale-dependent capability manifestation, with smaller nanostores showing stronger effects, and offers size-specific strategies, enhancing adaptability for smaller stores and agility for larger ones, providing actionable frameworks for the 185,000+ nanostores driving local economies.